Socialization of The Implementation of SAK EMKM and Digitalization of Marketing to Honey Farmers in Ayunan Village, Abiansemal District, Badung District - NARINDRA, A.A Ngurah Mayun; IDAWATI, Ida Ayu Agung; PARAMANANDA, N. (Indonesia Strategic Sustainability, 2024)
This study aims to improve the livelihoods of honey farmers in Ayunan Village by addressing their knowledge gaps in accounting and digital marketing. Through a participatory approach, it is hoped that the Implementation of the Community Partnership Empowerment Program (PKM) will be able to overcome the problems faced by honey farmer groups in Ayunan Village, Badung. The procedure for this PKM task is divided into three different stages: planning, task implementation, and result checking. Through tailored training and socialization, this study seeks to empower farmers to optimize their business operations, expand their markets, and contribute more significantly to the local economy. The implementation of community service in the Ayunan Village honey farmer group has had a significant positive impact. Through training in good financial reporting and socialization of SAK-EMKM, it is hoped that farmers will be able to manage business finances more effectively and efficiently. Thus, this study aims to be a model for the development of sustainable and profitable honey farming businesses in other rural areas.